Education Based Tourism Model at Pagilaran Tea Plantation, Keteleng Village, Batang Regency, Central Java, Indonesia - Rosardi, Raras Gistha; Prajanti, Sucihatiningsih Dian Wisika; Atmaja, Hamdan Tri; Juhadi (Indonesian Journal of Community Services Cel, 2022)
The phenomenon of traveling is now returning to nature, which is a beautiful and naturally identical environment in the village. Rural areas that offer special tourism potential become a separate tourist magnet for domestic tourists from urban and foreign countries.Pagilaran tea plantation is a natural potential of Batang regency which is administratively located in Pagilaran Hamlet, Keteleng Village, Blado District, Batang Regency. Pagilaran Tea Plantation should be one of the leading icons of Batang Regency to be maximized into agro-industry, agribusiness and agro-tourism. PT Pagilaran as part of Gadjah Mada University (UGM) has always been active in carrying out the mandate of the tri dharma of higher education in order to create a sustainable tea commodity plantation world, through various scientific studies by students, lecturers, and researchers as well as the empowerment of National Nuclear Plantation Farmers (Pir). Until now, The Pagilaran tea plantation is used as a place for student practice from the faculty of agriculture from several universities in indonesia. Educational and research activities are going well at the pagilaran tea plantation and there are even researchers from japan who are conducting research on tea plants at the Pagilaran Tea Plantation.